Has oral fluid the potential to replace serum for the evaluation of population immunity levels?: a study of measles, rubella and hepatitis B in rural Ethiopia - Nokes D. James; Enquselassie Fikre; Nigatu Wondatir; Vyse Andrew J.; Cohen Bernard J.; Brown David W.G; Cutts Felicity T. (The World Health Organization, 2001)
OBJECTIVE: To assess the suitability of using oral-fluid samples for determining the prevalence of immunity to vaccine-preventable infections. METHODS: Paired blood and oral-fluid samples were obtained from 853 individuals of all ages from a rural Ethiopian community. Oral fluid around the gums was screened for measles- and rubella-specific antibodies using enhanced IgG antibody capture (GAC) enzyme-linked immunosorbent assays (ELISAs), and for anti-HBc antibodies using a prototype GACELISA. IgG antibodies in serum to measles, rubella and HBc were determined using commercial ELISAs. FINDINGS: Relative to serum, oral fluid assay sensitivity and specificity were as follows: 98% and 87% for measles, 79% and 90% for rubella, and 43% and 87% for anti-HBc. These assay characteristics yielded population prevalence estimates from oral fluid with a precision equal to that of serum for measles (all ages) and rubella (ages <20 years). CONCLUSION: Our results suggest that oral fluid could have the potential to replace serum in IgG antibody prevalence surveys. Further progress requires assessment of variation in assay performance between populations as well as the availability of standardized, easy to use assays.